Structure of the immature HIV-1 capsid in intact virus particles at 8.8 Å resolution - Schur, Florian K M; Hagen, Wim J H; Rumlová, Michaela; Ruml, Tomáš; Müller, Barbara; Kräusslich, Hans-Georg; Briggs, John A G (Nature, 2015)
Human immunodeficiency virus type 1 (HIV-1) assembly proceeds in two stages. First, the 55 kilodalton viral Gag polyprotein assembles into a hexameric protein lattice at the plasma membrane of the infected cell, inducing budding and release of an immature particle. Second, Gag is cleaved by the viral protease, leading to internal rearrangement of the virus into the mature, infectious form. Immature and mature HIV-1 particles are heterogeneous in size and morphology, preventing high-resolution analysis of their protein arrangement in situ by conventional structural biology methods. Here we apply cryo-electron tomography and sub-tomogram averaging methods to resolve the structure of the capsid lattice within intact immature HIV-1 particles at subnanometre resolution, allowing unambiguous positioning of all α-helices. The resulting model reveals tertiary and quaternary structural interactions that mediate HIV-1 assembly. Strikingly, these interactions differ from those predicted by the current model based on in vitro-assembled arrays of Gag-derived proteins from Mason-Pfizer monkey virus. To validate this difference, we solve the structure of the capsid lattice within intact immature Mason-Pfizer monkey virus particles. Comparison with the immature HIV-1 structure reveals that retroviral capsid proteins, while having conserved tertiary structures, adopt different quaternary arrangements during virus assembly. The approach demonstrated here should be applicable to determine structures of other proteins at subnanometre resolution within heterogeneous environments.
Keywords: HIV-1; multimerizace proteinu; HEK293 buňky; Cryoelectron Microscopy; HEK293 Cells; Electron Microscope Tomography; Capsid Proteins; virové plášťové proteiny; virion; molekulární modely; Protein Multimerization; Models, Molecular; lidé; Virion; elektronová kryomikroskopie; konformace proteinů; kapsida; Humans; Capsid; tomografie elektronová; Masonův-Pfizerův opičí virus; Mason-Pfizer monkey virus; Protein Conformation; Virus Assembly; sestavení viru